Addition of dydrogesterone to vaginal progesterone and transfer postponement improve outcomes in patients with low progesterone levels in hormonally substituted cycles for frozen-thawed embryo transfer - Lecourt, Anne; Labrosse, Julie; Peigné, Maeliss; Laup, Laetitia; Sifer, Christophe; Grynberg, Michael; Cedrin-Durnerin, Isabelle (Clinical Journal of Obstetrics and Gynecology, 2022)
Purpose: Adding dydrogesterone (DYD) to vaginal micronized progesterone (VMP) and postponing embryo transfer in order to improve outcomes in patients with low progesterone (P) levels in hormonally substituted cycles prior to frozen/thawed embryo transfer (FET). Methods: Endometrial preparation comprised sequential administration of vaginal estradiol until endometrial thickness reached 7 mm, followed by transdermal estradiol combined with 800 mg/day VMP. Our previous analysis of serum P levels on FET day showed that the optimal P level was > 11 ng/mL for live birth. Serum P was measured on day 1 (D1) following exogenous VMP introduction in the evening. When P levels were > 11 ng/mL, FET was performed “in phase” on day-2, day-3, or day-5 depending on embryo stage at cryopreservation (n = 139 cycles). When P levels were < 11 ng/mL, DYD 10 mg three times a day orally, was added to VMP and FET was postponed by one day (n = 237 cycles, 63%). The primary endpoint was the comparison of live birth rates (LBR) between the two groups. Results: Mean serum P level on D1 was 10.2 + 3.7 ng/mL. Characteristics of patients in both groups were similar for age, body mass index, endometrial thickness prior to P introduction, quality of transferred embryos, and embryo transfer stage. Regarding the primary endpoint, LBR was similar between the VMP+DYD group and the VMP group (26.1% vs. 27.3%, NS). Conclusion: These results suggest that adding DYD to VMP and postponing the transfer in patients with low P levels in hormonally substituted FET cycles might optimize outcomes.